Ultrafast extreme ultraviolet photoemission without space charge - Christopher Corder; Peng Zhao; Jin Bakalis; Xinlong Li; Matthew D. Kershis; Amanda R. Muraca; Michael G. White; Thomas K. Allison (Structural Dynamics, 2018)
Time- and Angle-resolved photoelectron spectroscopy from surfaces can be used to record the dynamics of electrons and holes in condensed matter on ultrafast time scales. However, ultrafast photoemission experiments using extreme-ultraviolet (XUV) light have previously been limited by either space-charge effects, low photon flux, or limited tuning range. In this article, we describe XUV photoelectron spectroscopy experiments with up to 5 nA of average sample current using a tunable cavity-enhanced high-harmonic source operating at 88 MHz repetition rate. The source delivers >1011 photons/s in isolated harmonics to the sample over a broad photon energy range from 18 to 37 eV with a spot size of 58 × 100 μm2. From photoelectron spectroscopy data, we place conservative upper limits on the XUV pulse duration and photon energy bandwidth of 93 fs and 65 meV, respectively. The high photocurrent, lack of strong space charge distortions of the photoelectron spectra, and excellent isolation of individual harmonic orders allow us to observe laser-induced modifications of the photoelectron spectra at the 10−4 level, enabling time-resolved XUV photoemission experiments in a qualitatively new regime.